North Korea and the Enigma of Survival - Lee, Alex Taek-Gwang (Filozofski vestnik, 2018)
This paper sets out to balance the problematic “objective” status of North Korea on one hand as a “democratic” state (a democratic people’s republic), with its framing in liberal political discourse as a monstrous dictatorship on the other. The case of the Democratic People’s Republic of Korea is as complex and misleading as its name, and here I argue that in order to grasp the enigma of its survival as a political regime or dynasty, one must come to terms with the ongoing drive of Stalinist (pseudo-)socialist modernization that gripped the country after World War II, and which dovetails with North Korea’s Juche ideology of self-reliance.